(untitled) (Journal of Pathology of Nepal, 2022)
Filariasis is an infectious disease endemic in Nepal and the Indian subcontinent. However, filariasis of the breast is not very common. We present a case of a 24-year female with a breast nodule diagnosed with filariasis of the lymph node on the breast on histopathological examination. An infectious pathology should always be borne in mind in the endemic region for the timely management of the patient.